2003
DOI: 10.1081/ceh-120025334
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Natriuretic Response to Dopamine D1Receptor Agonist, SKF‐38393 in Obese Zucker Rats

Abstract: Dopamine causes natriuresis and diuresis via activation of D1 receptors located on the renal proximal tubules and subsequent inhibition of the sodium transporters, Na-H exchanger and Na+/K+ ATPase. We have reported that dopamine fails to inhibit the activities of these two transporters in the obese Zucker rats (OZR). The present study was designed to examine the functional consequence of this phenomenon by determining the natriuretic and diuretic response to D1 receptor activation in lean Zucker rats (LZR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
3
18
0
1
Order By: Relevance
“…6 In numerous studies, we have shown that dopamine D 1 receptor, which is known to increase tubular sodium excretion, is defective and unable to inhibit NKA activity in the PTs 18 and promote natriuresis in response to D 1 receptor agonist in obese rats. 33 Although D 1 receptor agonist was reported recently to promote AT 2 receptor translocation to the membrane and thereby enhance the AT 2 receptor function to promote natriuresis, 34 it is unlikely that defective D 1 receptor 18 contributed to the enhanced AT 2 receptor function as a compensatory mechanism in obese Zucker rats. 18 Similarly, an upregulation of the renal AT 2 receptor function on tubular sodium metabolism was found in streptozotocin-induced diabetic rats, 35 where dopamine D 1 receptors also are shown to be defective.…”
Section: Discussionmentioning
confidence: 99%
“…6 In numerous studies, we have shown that dopamine D 1 receptor, which is known to increase tubular sodium excretion, is defective and unable to inhibit NKA activity in the PTs 18 and promote natriuresis in response to D 1 receptor agonist in obese rats. 33 Although D 1 receptor agonist was reported recently to promote AT 2 receptor translocation to the membrane and thereby enhance the AT 2 receptor function to promote natriuresis, 34 it is unlikely that defective D 1 receptor 18 contributed to the enhanced AT 2 receptor function as a compensatory mechanism in obese Zucker rats. 18 Similarly, an upregulation of the renal AT 2 receptor function on tubular sodium metabolism was found in streptozotocin-induced diabetic rats, 35 where dopamine D 1 receptors also are shown to be defective.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Briefly, rats were anesthetized using Inactin (100 to 160 mg/kg IP). The left jugular vein and carotid artery were cannulated for saline/drug infusion and blood pressure measurement, respectively.…”
Section: Kidney Function Experiments Protocolmentioning
confidence: 99%
“…Surgical procedures were carried out as described earlier. 17 Urine samples were collected throughout the 30-minute periods, and blood samples were collected at the end of each period. Renal function was evaluated as described previously.…”
Section: Experimental Protocol For Renal Function Studiesmentioning
confidence: 99%